Evaluation of Educational Reforms and Human Capital Development in a Global Age - Obagah, M.O.N (Richtmann Publishing, 2012)
Our concern is lecture is basically an evaluation of the National 10 – year Development Plan onEducational Reforms and The part of NEEDS policy on the making of Millennium Development Goals.MDGs in 2005. The Policy provisions were critically evaluated as to what extent they have gone midwayinto the Targeted year 2015. It was found that by year 2010, the implementers of these 10 – years –Development plan have not gone near 45% of what should be 100% by 2015. The UBE and MDGs goalsmay end up as mere pipe dreams and a drain on the national resources if double Efforts are not made nowto strengthen the resolve to achieve these set goals. It was recommended that all the policy options in allthe section of our educational system must be vigorously pursued in order to attain these goals we have setfor our nation Nigeria